Dynamics of phytoplankton in estuaries and changes in environmental driving factors: a study of Lianzhou Bay in Guangxi, China - Youyin Ye; Yongqiang Tian; Qianqian Zhou; Yanghang Chen; Yu Wang; Bingpeng Xing; Cun Jia; Peng Xiang; Xuebao He (Frontiers in Marine Science)
To investigate the impact of freshwater discharge variations from the Nanliu River on the phytoplankton community structure in Lianzhou Bay, we conducted surveys of total chlorophyll-a (Tchl-a) concentrations and specific pigment groups during wet and dry seasons of 2016. During wet season, freshwater discharge introduced substantial freshwater, nutrients, and suspended particulate matter into Lianzhou Bay. Due to reduced light availability, Tchl-a concentrations at most stations were lower compared to dry season. The result indicated that light availability often exerts a greater influence than nutrient availability in estuarine environments. Furthermore, the spatial distribution of Tchl-a concentrations in Lianzhou Bay is correlated with the feeding activities of bivalve aquaculture and water movement within the bay. During the high-water period, the phytoplankton community was primarily composed of diatoms (35.0%), cyanobacteria (21.0%), prasinophytes (13.0%), chlorophytes (19.0%), and cryptophytes (11.0%). In contrast, the low-water period saw a phytoplankton community dominated by diatoms (62.0%), prasinophytes (18.0%), cyanobacteria (12.0%), and cryptophytes (7.0%). The absence of osmotic regulation in chlorophytes restricts their distribution primarily to estuarine environments characterized by high water availability. In contrast, diatoms exhibit a greater affinity for well-illuminated conditions, thereby contributing significantly to primary productivity in neritic zones and during periods of low water flow.